2016
DOI: 10.1371/journal.pone.0166281
|View full text |Cite|
|
Sign up to set email alerts
|

Associations of Infant Feeding and Timing of Weight Gain and Linear Growth during Early Life with Childhood Blood Pressure: Findings from a Prospective Population Based Cohort Study

Abstract: ObjectiveSmall birth size and rapid postnatal growth have been associated with higher future blood pressure. The timing of these effects, the relative importance of weight gain and linear growth and the role of infant feeding need to be clarified.MethodsWe assessed how blood pressure relates to birth weight, infant and childhood growth and infant feeding (duration of exclusive breastfeeding and timing of introduction of complementary feeding) in 2227 children aged 5 years from a prospective cohort study (Amste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 43 publications
(70 reference statements)
4
10
1
1
Order By: Relevance
“…[56][57][58][59] Our estimates of the association of interest were higher when BP was measured in sitting rather than supine posture. Our results with regard to SBP are in line with the results found by De Beer et al 27 They also found an association with DBP, but we could not confirm this. Furthermore, the results of our study are in line with our previous study of healthy young children, where we showed that higher VAT resulted in higher sitting SBP values.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…[56][57][58][59] Our estimates of the association of interest were higher when BP was measured in sitting rather than supine posture. Our results with regard to SBP are in line with the results found by De Beer et al 27 They also found an association with DBP, but we could not confirm this. Furthermore, the results of our study are in line with our previous study of healthy young children, where we showed that higher VAT resulted in higher sitting SBP values.…”
Section: Discussionsupporting
confidence: 76%
“…25,26 The results of two studies suggested that there is also an association between WLG during the first 3 months of life and BP. 27,28 It is important to reveal the origin of BP variations in population to prevent hypertension and CVD. Deeper understanding of the impact of growth patterns early in life may contribute to better cardiovascular health from early life onward.…”
Section: Introductionmentioning
confidence: 99%
“…The PROBIT study that followed children up to the age of 6.5 years showed that EBF duration had no effect on blood pressure [2]. In contrast, other studies broadly support that longer breastfeeding, but < 24 months, and subsequent delayed introduction of CF were related to lower waist circumference and blood pressure in early life [74,75]. Recent studies have also evaluated the specific role of LC-PUFA and fat intake during CF in later cardiometabolic health.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…In total, five studies found a significant association between increased weight gain in different periods between birth and 4 years of age, and lower BP in adolescence and adulthood (Table 1). 29,[33][34][35][36] However, the vast majority of studies, including a meta-analysis of five cohort studies reports that postnatal weight gain is associated with higher BP later in life, especially when early and excessive 24,31,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] (Table 1).…”
Section: Effect Of Postnatal Excessive Growth On Bp In Children With mentioning
confidence: 99%